Al-Farabi on the interdependence of religion and politics (Journal of Philosophy Culture and Political Science, 2019)
Abu Nasr Muhammad b. Muhammad, better known as al-Farabi (c.870 -c.950), was the most au- thentic of the Arabic philosophers. The principal sources of his philosophy are to be sought in the Greek tradition, in the original writings of Plato and Aristotle, in Neoplatonism and Aristotelianism of Alex- andria. Most significant is his turn towards the much undervalued Middle Platonism. His main thesis consists in the preponderance of philosophy over theology. Religion is used as a substitute for philoso- phy, as the complex and abstract notions of the latter are difficult to grasp. Religion attempts to express philosophical truths with the aid of imagination. Along with the support of jurisprudence and politics, it has taken upon itself to guide the ignorant, that is, the largest part of the population, towards the attain- ment of happiness. Political and social problems become overwhelming when legislators are under the sway of religious beliefs and do not realize the need to base their legislation on philosophy, rather than religion. In this paper, we are attempting to present, analyze and evaluate the views of al-Farabi on the interaction between religion and politics.Key words: philosophy, political philosophy, virtuous city, virtuous state, religion and politics.